Efficient Design of a Large Storage Tank for Liquefied Natural Gas (Journal of University of Babylon for Engineering Sciences, 2018)
Natural gas is known as a green source of energy due to high purity, high energy density and environment friendly. To transport natural gas, it is an important to convert it into liquid case to reduce the cost, therefore the design of storage tank can be important factor in the natural gas trade. Liquefied natural gas (LNG) tank as a kind of storage column is quite different with other storage columns. Firstly, the size of this type of LNG tank is highly large, which comes with capacity up to 200,000 m3. LNG storage tank can be considered as a new technique in this field for many countries. Secondly, the low temperature of LNG will increase the isolation part and lead to difficult process through the operation and installation time. This work combines different designs codes to study in details the LNG tank design in terms of inner and outer construction, bottom design with corner protection, and top design with corner protection. In addition, the heat leakages have been calculated for each part to show that the heat leakage is acceptable.